How Viscoelastic Effects Impact Polymer Fluid Flow in Porous Media - Yongxin Wang; Si Suo; Callum Cuttle; Christopher W. MacMinn; Martin J. Blunt; Catherine O’Sullivan (Transport in Porous Media, 2026)
Polymer fluids are widely used in subsurface and geotechnical engineering applications. While the steady shear rheology of polymer fluids is known to be reasonably captured by a Carreau-like shear-thinning model, it is still not fully understood how their elastic rheological characteristics, beyond shear-thinning behavior alone, influence their flow in porous media. In this study, we numerically investigate these effects using direct, pore-scale numerical simulations. By comparing data from simulations using the FENE-P model, which incorporates viscoelastic effects, with data from corresponding simulations using the Carreau model, which captures only shear thinning, we confirm that fluid elasticity can induce recirculation upstream of restrictions, leading to a reduction in polymer fluid conductance in porous media. As this recirculation is controlled by the geometric conditions, we conducted detailed comparisons between a two-dimensional model, a three-dimensional model mimicking microfluidics experiments, and an axisymmetric model, analogous to a constricted capillary tube. We also simulate flow in an ordered packing of uniform spheres to develop an understanding of the implications for flow in a 3D porous material. We find that these flows are regulated by the interplay between shear-thinning and elasticity effects. When the shear-thinning effect is sufficiently strong, the effects of elasticity are suppressed. In subsurface applications, viscoelastic effects are significant due to pore-scale confinement and fluid rheology itself, requiring explicit consideration in modeling, pilot design, and performance forecasting. Article Highlights In porous media, the pore geometries control the flow patterns of polymer fluids that have both shear-thinning and elastic characteristics. Upstream recirculation in a single-constriction channel induced by elastic forces takes place in wider pore spaces and develops with increasing Weissenberg number. For flow through a quasi-3D single constriction and a regular lattice packing, a greater energy loss is observed in the case of viscoelastic fluids in comparison with that in the corresponding Carreau fluid. The ratio of the zero-shear-rate viscosity to the infinite-shear-rate viscosity changes the polymer fluid conductance and flow patterns in a single-constriction channel. The extent of the upstream recirculation is proportional to the excessive pressure gradient in the viscoelastic fluid over the corresponding equivalent Carreau fluid.